PROSES INOVASI KURIKULUM DAN PEMBELAJARAN - Rachmad, Ferizal; Mansur, Amril; Bakar, Abu (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this study is to describe the process of curriculum innovation and learning. This study uses the method of literature review. The results of the study show that the innovation process is absolutely necessary for various levels of education. In the implementation of innovation requires diffusion and dissemination. The existence of globalization, developments in science and technology, problems that develop in society and needs in the business world as well as the world of work and industry must be answered by the world of education. This is also the basis for the S1 Management Study Program FEIS UIN SUSKA Riau to quickly respond to developments in the national and global economy by innovating the curriculum.